Clinicopathological profile of dengue fever among children admitted in Medical College for Women & Hospital, Dhaka, Bangladesh: Clinicopathological profile of dengue fever among children (Journal of the Medical College for Women & Hospital, 2024)
Background: Dengue is not always manifested by its typical clinical features, its presentation may be atypical which may create confusion among physicians while making a diagnosis. The clinical profile that was seen in earlier epidemics has changed over time and various atypical features are found in day to day clinical practice. The trends in simple hematological and biochemical parameters are of utmost importance to evaluate the severity of the disease. Aim:This study was carried out to evaluate the clinico-pathological profile of dengue fever in children.Materials and Method: This cross-sectional study was conducted in the department of Paediatrics, of Medical College for Women and Hospital, Uttara, Dhaka, from August to October 2023 following ethical clearance of the protocol. A total of 250 children aged 0-18 years attended in the study center with fever with positive NSI  (nonstructural protein 1) antigen or positive IgM (Immunoglobulin M) antibody of dengue were included after getting informed written consent from their legal guardians. Data were collected by using a structured questionnaire. Collected data were analyzed by the SPSS 26.Result: The mean±SD of age of the respondents was 7.12±4.26 year with male predominance (54.8%). All respondents had fever, wherein majority had low grade fever (67.2%). More than half of the respondents (52.4%) had vomiting. Oral thrush (42.8%), abdominal pain (34%), congestion of the eye (28.4%), runny nose (22.4%), cough (16%), headache (15.6%), rash (14.8%), lack of appetite (14%) and loose stool (13.6%) were the other common clinical features. Pleural effusion (15.6%) in Chest X-ray and respiratory distress (28.8%) and ascites (17.6%) were other common findings. Hepatomegaly, ascites, respiratory distress, pleural effusion and edematous gallbladder were significantly more in severe dengue than non-severe dengue fever. Besides, decreased Hb% (hemoglobin %), increased HCT (hematocrit) level, SGPT (Serum Glutamic Pyruvic Transaminase) >56U/L and SGOT (Serum Glutamic Oxalo-Acetic Transaminase) >45U/L were significantly higher in severe dengue fever than non-severe dengue.Conclusion: Dengue in children presented with diverse symptoms and severity. However, further multicenter study is recommended to verify the present findings.J Med Coll Women Hosp.2024; 20(2): 44-55